Comparison of compensatory reserve and arterial lactate as markers of shock and resuscitation. Issue 4 (October 2017) - Johnson, Michael Craig; Alarhayem, Abdul; Convertino, Victor; Carter, Robert; Chung, Kevin; Stewart, Ronald; Myers, John; Dent, Daniel; Liao, Lilian; Cestero, Ramon; Nicholson, Susannah; Muir, Mark; et al.
Abstract : BACKGROUND: During traumatic hemorrhage, the ability to identify shock and intervene before decompensation is paramount to survival. Lactate is extremely sensitive to shock, and its clearance has been demonstrated a useful gauge of shock and resuscitation status. Though lactate can be measured in the field, logistical constraints render it impractical in certain environments. The compensatory reserve represents a new clinical measurement reflecting the remaining capacity to compensate for hypoperfusion. We hypothesized the compensatory reserve index (CRI) would be an effective surrogate marker of shock and resuscitation compared to lactate. METHODS: The CRI device was placed on consecutive patients meeting trauma center activation criteria and remained on the patient until discharge, admission, or transport to operating suite. All subjects had a lactate level measured as part of their routine admission metabolic analysis. Time-corresponding CRI and lactate values were matched in regards to initial and subsequent lactate levels. Mean time from lactate sample collection to data availability in the electronic medical record was calculated. Predictive capacity of CRI and lactate in predicting hemorrhage was determined by receiver-operator characteristic curve analysis. Correlation analysis was performed to determine if any association existed between changing CRI and lactate values. RESULTS: Receiver-operator characteristic (ROC) curves were generated and area under the curve was 0.8052 and 0.8246 for CRI and lactate, respectively. There was no significant difference in each parameter's ability to predict hemorrhage ( p = 0.8015). The mean duration from lactate sample collection to clinical availability was 44 minutes whereas CRI values were available immediately. Analysis of the concomitant change in serial CRI and lactate levels revealed a Spearman's correlation coefficient of −0.73 ( p < 0.01). CONCLUSION: CRI performed with equivalent predictive capacity to lactate with respect to identifying initial perfusion status associated with hemorrhage and subsequent resuscitation. LEVEL OF EVIDENCE: Diagnostic, Level II.